Relation between Depression Status with Mini Nutritional Assessment Scores (MNA) in Elderly People in Panti Wredha Dharma Bhakti Surakarta - Nurhidayah, Siti; Suhanantyo, .; Afifah, Zulaika Nur (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2016)
Background. Malnutrition is a common problem for the elderly. This can be caused by a variety of physical, social, and psychological factors. Psychological factor such as depression often causes a decrease in appetite and food intake that affect the nutritional status of elderly and increase the risk of malnutrition. This study aimed to determine the relation between depression status with Mini Nutritional Assessment scores (MNA) in elderly people in Panti Wredha Dharma Bhakti Surakarta. Method. This was an observational analytic study with cross sectional design. Population were 90 elderlies aged over 60 years who lived in Panti Wredha Dharma Bhakti Surakarta. The sampling technique used purposive sampling and obtained a sample of 33 elderly. Data were obtained through direct interviews using Geriatric Depression Scale-15 (GDS-15) questionnaires to determine the depression status of elderly and Mini Nutritional Assessment (MNA) questionnaires to determine the nutritional score of the elderly. Statistical analysis using unpaired t test. Result. From the 33 samples, this study found that 27 elderlies (81.8 %) do not have depression while other 6 elderly (18.2 %) have depression. Elderly who have malnourished were 2 persons (6.1 %), the risk of malnutrition were 21 people (63.6 %), and well-nourished were 10 people (30.3 %). Unpaired t test results showed no significant relation between depression status with MNA scores in elderly people in Panti Wredha Dharma Bhakti Surakarta (p > 0.05). There is no significant relation between either age, gender, and level of education with MNA scores (p > 0.05). Conclusion. There is no relation between depression status with MNA scores in elderly people in Panti Wredha Dharma Bhakti Surakarta. Â Keywords: depression, malnutrition, elderly Â